MENGEMBANGKAN KETERAMPILAN MENGGUNTING DENGAN KOMBINASI MODEL PROJECT BASED LEARNING, DIRECT INSTRUCTION DAN MEDIA KERTAS BERGAMBAR - Anisa, Nor; Sulistiyana, Sulistiyana (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
This research is based on the low fine motor ability in scissors activities according to the pattern in Group B, the solution to solve this problem is by using a combination of Project Based Learning, Direct Instruction models with illustrated paper media. The purpose of this study is to describe teacher activities, children's activities and the results of children's fine motor development. The approach used is a qualitative approach with the type of Classroom Action Research (PTK) with 4 meetings. Data analysis showed that teachers' activities achieved a score of 40 with the criterion of